Penerapan Steganografi untuk Pengamanan Konten Gambar dalam Media Sosial - Gede Eka Putra Wijaya,; I Gusti Agung Gede Arya Kadnyanan, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
The rapid development of technology has significantly impacted various aspects of life, especially social media. Social media platforms are not only used for interaction but also for building branding through content uploads. However, this raises concerns about unauthorized use of content that violates Intellectual Property Rights (IPR). Digital watermarking using steganography, specifically the Least Significant Bit (LSB) technique, can protect content by hiding messages without degrading visual quality. This study tests the insertion of text into digital images using two sample logos of different sizes. The test results show Mean Square Error values ranging from 1.8 to 2 and Peak Signal-to-Noise Ratio values between 94.9 and 95.3, indicating excellent visual quality and almost imperceptible differences. This technique effectively protects content from unauthorized use.
Keywords: Steganography, Least Significant Bit (LSB), Social Media content, Digital Watermarking, Intellectual Property Rights (IPR)